1992
DOI: 10.1029/92gl01159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial liquid/gas saturation on extensional wave attenuation in Berea sandstone

Abstract: Extensional wave attenuation measurements on Berea sandstone were made during increasing (imbibition) and decreasing (drainage) brine saturations. Measurements on samples with both open‐pore and closed‐pore surfaces were made using the resonant‐bar technique. The frequency dependence was examined using the forced‐deformation method. The attenuation was found to be dependent on saturation history as well as degree of saturation and boundary flow conditions. The sample with open‐pore surface had a larger attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 28 publications
7
43
1
8
Order By: Relevance
“…More details on sample sealing can be found in Tisato and Quintal (2013). Dunn (1987) and Yin et al (1992) show that a layer of glue or a metal foil glued on the external surface of the sample limits the free-flow boundary effect that could bias the measurements (Gardner, 1962;Dunn, 1986). On the other hand, Tisato and Madonna (2012) discuss that, for the considered rock and conditions, this effect should be significant only at frequencies higher than 100 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…More details on sample sealing can be found in Tisato and Quintal (2013). Dunn (1987) and Yin et al (1992) show that a layer of glue or a metal foil glued on the external surface of the sample limits the free-flow boundary effect that could bias the measurements (Gardner, 1962;Dunn, 1986). On the other hand, Tisato and Madonna (2012) discuss that, for the considered rock and conditions, this effect should be significant only at frequencies higher than 100 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…The fluid accumulation should have a direct effect in the attenuation because many experimental studies have demonstrated that behavior (Frisillo and Stewart 1980;Tittmann et al 1980;Yin et al 1992;Dilay and Eastwood 1995). Although not all volcanic crises require gas accumulation, we suggest that those volcanic crises associated with eruptions, ash emission, or strong swarms of LP events or hybrid events should involve some portion of gas accumulation.…”
Section: Application Of the Warning Model For Nevado Del Ruiz Volcanomentioning
confidence: 97%
“…Experimental studies demonstrated that Q -1 is very sensitive to changes in the gas content and partial saturation in rocks (Devilbiss-Muñoz 1980;Frisillio and Stewart 1980;Yin et al 1992). Dilay and Eastwood (1995) seismically monitored attenuation during a steam flood used for oil production.…”
Section: The Construction Of the Warning Modelmentioning
confidence: 99%
“…The predicted attenuation increases with increasing permeability, but the location of the peak has little change. Yin et al [31] concluded that the peak is strongly dependent on the history of saturation. During the drainage the attenuation reaches a maximum at about 90% water saturation, and for imbibition the attenuation peak shifts toward a higher water saturation around 97%.…”
Section: Comparison With Experimental Datamentioning
confidence: 98%